The Impact Of Budget Efficiency On The Psychological Well-Being Of Soldiers Of Infantry Battalion 733/Masariku In The Context Of The Indonesia–Papua New Guinea Border Security Task Force - Roy Astyanto; Adv Bangun P. Hutajulu (CV RIFAINSTITUT, 2026)
Budget efficiency policies in the defense sector, particularly those reducing psychological support programs, have raised concerns regarding their impact on soldiers' mental resilience in high-risk operational environments. This study examines the psychological implications of such policies on personnel of Infantry Battalion 733/Masariku deployed in the Indonesia–Papua New Guinea Border Security Task Force. A qualitative descriptive approach was employed using document analysis, policy review, and recent literature. The study applied a SWOT (Strengths, Weaknesses, Opportunities, Threats) framework to systematically evaluate internal and external factors influencing soldiers' psychological well-being. Data were analyzed through thematic categorization and strategic mapping to identify key patterns and relationships. The findings indicate that despite strong internal factors such as leadership, discipline, and unit cohesion, budget reductions have weakened psychological assessment, pre-deployment preparation, and mental health monitoring. The SWOT analysis places the organization in Quadrant I (growth-oriented strategy), suggesting that strengths and opportunities outweigh weaknesses and threats. Key adaptive strategies include optimizing leadership roles as mental coaches, integrating psychological development into routine activities, and leveraging peer support systems. The study highlights that psychological resilience can be maintained through cost-effective and embedded approaches, even under fiscal constraints. Leadership engagement, interpersonal communication, and organizational culture play critical roles in mitigating stress and sustaining morale.